Hubungan Usia dan Paritas Ibu Hamil dengan Kelengkapan Pemeriksaan Antenatal Care (ANC) di Desa Kualu Wilayah Kerja Puskesmas Tambang Kabupaten Kampar - Sriwidya Astuti Khati; Adelia Nopriyarti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
According to the 2023 Indonesian Health Profile, health services for pregnant women (K1-K6) in 2023 in Indonesia will be 74.4% with the 2023 Minimum Service Standard (SPM) target of 100%, still far from the standard. Factors influencing ANC visits for pregnant women are age and parity. The aim of this research is to find out the mother's age and parity with the completeness of the ANC examination. This type of research is quantitative using a cross sectional approach. The population in this study was 60 pregnant women in the third trimester in Kualu Village. The sample consisted of 60 pregnant women in the third trimester with a gestational age of 37-39 weeks using total sampling. The data collection tool uses a questionnaire. This research uses univariate and bivariate analysis with the chi-square test. The univariate research results show that 34 respondents (56.7%) are in the no-risk category and maternal parity is not at risk < 3 times. Bivariate results. There is a significant relationship between maternal age and completeness of ANC examinations and there is a relationship between maternal parity and completeness of ANC examinations. It is hoped that midwives and cadres will provide education and programs to attract pregnant women to come for ANC examinations.